Female Religious Practices, Agency, and Freedom in the Novel Jin ping mei - Beaudoin, Crystal Marie (My University, 2017)
In the patriarchal milieu of sixteenth-century China, women demonstrated agency in their families and communities through their religious practices. Male family members typically performed Confucian rites related to ancestor veneration; yet there were many opportunities for women to participate in practices associated with other religious traditions. In this study, I will elucidate the religious roles of women during the late Ming dynasty (1368—1644 CE). Using the cultural-historical method, I will demonstrate the ways in which women gained agency and freedom from social conventions through their religious practices. By comparing literary sources with historical documents, I will validate the use of my major literary source, Jin ping mei, to study the religious practices in sixteenth-century China. This study will provide scholars with a nuanced understanding of gender roles within upper-class families in early modern China. Women were not simply passive, submissive members of a Confucian society; rather, they often gained authority and autonomy within their families and communities.
Keywords: Jin ping mei; Ming dynasty; Chinese religions